2004
DOI: 10.1159/000077377
|View full text |Cite
|
Sign up to set email alerts
|

Selective Expression of TGF-β2 and TGF-β3 Isoforms in Early Mesangioproliferative Glomerulonephritis

Abstract: Background/Aim: Evidence from ex vivo glomerular analysis has implicated overexpression of transforming growth factor (TGF) beta 1 in progressive renal disease. The roles of TGF-β2 and TGF-β3 are less clear. The purpose of this study was to define the temporal expression and abundance of TGF-β isoforms in both acute and progressive Thy-1 glomerulonephritis during the crucial initiation phase of these models. Methods: Acute Thy-1 glomerulonephritis was induced by a single injection of OX7, while the progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The TGF-␤1, TGF-␤2, and TGF-␤3 primary antibodies obtained have been shown previously to be specific and possess no crossreactivity for the individual TGF-␤ isoforms in the rat species. 15,16 Tissue sections were deparaffinized and rehydrated in graded ethanol. Endogenous peroxide activity was quenched with 3% hydrogen peroxide in phosphate-buffered saline for 5 minutes, followed by three washes in phosphatebuffered saline.…”
Section: Histologic Examinationmentioning
confidence: 99%
“…The TGF-␤1, TGF-␤2, and TGF-␤3 primary antibodies obtained have been shown previously to be specific and possess no crossreactivity for the individual TGF-␤ isoforms in the rat species. 15,16 Tissue sections were deparaffinized and rehydrated in graded ethanol. Endogenous peroxide activity was quenched with 3% hydrogen peroxide in phosphate-buffered saline for 5 minutes, followed by three washes in phosphatebuffered saline.…”
Section: Histologic Examinationmentioning
confidence: 99%
“…Groups of two mice were killed at weekly intervals, with kidneys evaluated for apoptosis and expression of clusterin, fibroblasts (monoclonal antibody ER/ TR7 59 ), and HSP-47 as a marker for increased collagen synthesis. 41 Kidneys were processed and stained using previously described methods, 60,61 which will be briefly described. Immunohistochemical staining for clusterin (b-chain specific, Santa Cruz Biotechnology, Santa Cruz, CA, USA) was conducted using a Vectastain Elite ABC kit (Vector Laboratories, Burlingame, CA, USA) with some modifications.…”
Section: Bsa Overload In Micementioning
confidence: 99%
“…In earlier studies, we have shown that glomerular mesangial cells express and secrete both LTBP-1 and fibrillin-1 in vitro [6]. Further, we and others have demonstrated an induction of TGF-β isoforms during experimental anti-Thy1.1 glomerulonephritis, which is characterized by transient mesangial hypercellularity and mesangial matrix expansion [7, 8]. We hypothesized that LTBP-1 and fibrillin-1 are coexpressed in the mesangial matrix and are upregulated during acute anti-Thy1.1 glomerulonephritis.…”
Section: Introductionmentioning
confidence: 99%